1930
DOI: 10.1084/jem.52.4.519
|View full text |Cite
|
Sign up to set email alerts
|

Studies on a-Avitaminosis in Chickens

Abstract: 1. The principal tissue changes in the respiratory tract of chickens caused by a vitamin A deficiency in the food are, first, an atrophy and degeneration of the lining mucous membrane epithelium as well as of the epithelium of the mucous membrane glands. This process is followed or accompanied by a replacement or substitution of the degenerating original epithelium of these parts by a squamous stratified keratinizing epithelium. This newly formed epithelium develops from the primitive columnar epithelium and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

1931
1931
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 3 publications
(1 reference statement)
2
7
0
Order By: Relevance
“…2,7 Gross lesions are initially confined to the mucous glands and ducts of the pharynx and esophagus and appear as white to yellowish caseous, coalescing nodules. 11,18,19 Microscopically, squamous metaplasia is the hallmark of vitamin A deficiency (VAD), affecting the cuboidal and columnar epithelia of the mucosal glands of the digestive, respiratory, and urinary tracts and the eye. 3,8,10,18,19 Natural and experimental VAD are well documented in chickens but a natural occurrence and histopathological description of this condition has not been reported in commercial turkeys.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2,7 Gross lesions are initially confined to the mucous glands and ducts of the pharynx and esophagus and appear as white to yellowish caseous, coalescing nodules. 11,18,19 Microscopically, squamous metaplasia is the hallmark of vitamin A deficiency (VAD), affecting the cuboidal and columnar epithelia of the mucosal glands of the digestive, respiratory, and urinary tracts and the eye. 3,8,10,18,19 Natural and experimental VAD are well documented in chickens but a natural occurrence and histopathological description of this condition has not been reported in commercial turkeys.…”
mentioning
confidence: 99%
“…11,18,19 Microscopically, squamous metaplasia is the hallmark of vitamin A deficiency (VAD), affecting the cuboidal and columnar epithelia of the mucosal glands of the digestive, respiratory, and urinary tracts and the eye. 3,8,10,18,19 Natural and experimental VAD are well documented in chickens but a natural occurrence and histopathological description of this condition has not been reported in commercial turkeys. This report is an account of the gross and histopathological changes caused by VAD in commercial turkeys.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a striking fact that in many instances the affected nuclei underwent dissolution. We have not observed similar changes of epithelial cells in other diseases involving the same structures, such as A-avitaminosis, coryza contagiosa, and fowlpox (12,13). Since the same type of intranuclear inclusions and nuclear changes are present in other virus diseases, we feel justified in considering them a result of virus activity in the epithelial cells of the trachea and larynx.…”
Section: Intranuclear Inclusions In Epithelial Cells Of the Respiratomentioning
confidence: 56%
“…On the other hand, Sugiura and Benedict (1923) state that the fat-soluble vitamin is not essential in any stage of avian nutrition. However, this view is not supported by other investigators, for Emmett and Peacock (1923), Hart, Steenbock, Lepkovsky, and Halpin (1924), Hughes, Lienhardt, andAubel (1929), Capper, McKibbin, andPrentice (1931), Elvehjem and Neu (1932), Seifried (1930), Hauge, Carrick, and Prange (1927), Frohring and Wyeno (1934), and others have shown that vitamin A is essential for the proper development of young chicks and that growing chicks which are limited for any length of time to rations that are inadequate or lacking in vitamin A develop characteristic symptoms of A-avitaminosis.…”
mentioning
confidence: 91%